2021
DOI: 10.48550/arxiv.2109.04120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Privacy-Protecting Techniques for Behavioral Biometric Data: A Survey

Abstract: Our behavior -the way we talk, walk, or think-is unique and can be used as a biometric trait. It also correlates with sensitive attributes like emotions. Hence, techniques to protect individuals' privacy against unwanted inferences are required. To consolidate knowledge in this area, we systematically reviewed applicable anonymization techniques. We taxonomize and compare existing solutions regarding privacy goals, conceptual operation, advantages, and limitations. Our analysis shows that some behavioral trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 140 publications
(188 reference statements)
0
11
0
Order By: Relevance
“…The authors survey anonymization methods that they identified in the literature analysis to mitigate the two main identified privacy threats, namely identity disclosure to identify the user in another scenario and attribute disclosure to derive sensitive attributes form the behavioural biometrics. They give in the actualized paper version [73] of [24] an overview table indicating for the related privacy goals identity and attribute protection the different techniques that try to achieve these goals.…”
Section: Biometric Schemesmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors survey anonymization methods that they identified in the literature analysis to mitigate the two main identified privacy threats, namely identity disclosure to identify the user in another scenario and attribute disclosure to derive sensitive attributes form the behavioural biometrics. They give in the actualized paper version [73] of [24] an overview table indicating for the related privacy goals identity and attribute protection the different techniques that try to achieve these goals.…”
Section: Biometric Schemesmentioning
confidence: 99%
“…The authors grounded their work on "two main privacy threats that apply to behavioural data collected/processed by a third party", identity disclosure and attribute disclosure, which are in line with the PB3 Unlinkable and PB4 Resilient-to-Identifiability that we defined. In the actualized paper version [73], the authors provide an overview table indicating the privacy goals that the different techniques try to achieve.…”
Section: Sample Evaluation Of Authentication Schemes With the Udsp Fr...mentioning
confidence: 99%
See 3 more Smart Citations